Quality of Life and Fitness in Children and Adolescents with Epilepsy (EpiFit) - Rauchenzauner, Markus; Hagn, Claudia; Walch, Romana; Baumann, Matthias; Haberlandt, Edda; Frühwirth, Martin; Rostasy, Kevin (Neuropediatrics, 2017)
Objective The objective of this study was to evaluate the correlation between fitness and health-related quality of life (HRQoL) in children with idiopathic epilepsy compared with a healthy matched control group.Methods In this study, 107 children conducted a 6-minute walk test, anthropometric parameters were measured, and HRQoL was assessed using a standardized questionnaire (KINDL-R). Children were divided into two groups: (1) the patient group (n = 48) and (2) the healthy control group (n = 59).Results HRQoL of children with focal epilepsy was greater when compared with healthy children and children with generalized epilepsy. A significant association could be demonstrated for the 6-minute walk distance and mental wellbeing in children with epilepsy but not in healthy children. Furthermore, a negative correlation between the HRQoL and the amount of time spent in front of TV and computer in children with epilepsy and healthy children was seen. In children with focal epilepsy, a significant negative correlation could be shown between school sport and mental wellbeing as well as between school sport and self-esteem.Conclusion HRQoL in children with idiopathic epilepsy is significantly associated with physical fitness and might be positively influenced by an adequate education of patients and parents, a reduction of consumption of computer and TV in combination with age- and disease-adapted physical activity and sports.
Keywords: epilepsy; children; sports; health-related quality of life